COGNITIVE FUNCTIONS IN GENERAL HEAT INJURY - Мізякіна, Катерина; Єхалов, Василій; Кравець, Ольга; Баклицька, Олександра (SWorldJournal, 2023)
Based on the results of foreign research and their own clinical experience, the authors were able to highlight the main patterns of occurrence, course and prognosis of disorders of cognitive functions in victims of heat stress and heat stroke.